Penyuluhan dan Pelatihan Penggunaan Obat Tradisional serta Penerapan Hasil Penelitian Tumbuhan Sungkai (Peronema canescens Jack) kepada Masyarakat - Dwisari Dillasamola; Yufri Aldi; Fatma Sri Wahyuni; Hansen Nasif; Yohannes Alen (Warta Pengabdian Andalas, 2023)
Indonesians, particularly those residing in rural areas with abundant plant diversity, have long relied on traditional medicine that utilizes plants. Sungkai (Peronema canescens Jack.) is one example of a widely-used traditional medicine known for its immunity-boosting properties. However, many people need more awareness of the potential benefits and risks of plants like Sungkai, so it is necessary to provide education and training to promote proper usage and ensure public safety. This community service activity aimed to equip individuals with the knowledge and skills to process plants accurately, utilize them appropriately based on the severity of the illness, and avoid any adverse side effects or toxicity. The counselling method used in this initiative involves lectures, which is effective for individuals with varying education levels, especially the general public. This program has yielded promising results, with the community displaying strong enthusiasm for the initiative. Ultimately, education and counselling services can significantly improve public understanding and use of traditional medicine.